Prevalence and adverse outcomes of twin pregnancy in Eastern Africa: a systematic review and meta-analysis - Tamirat Getachew; Abraham Negash; Adera Debella; Elias Yadeta; Magersa Lemi; Bikila Balis; Tegenu Balcha; Habtamu Bekele; Mohammed Abdurke; Addisu Alemu; Kasiye Shiferaw; Addis Eyeberu (BMC, 2024)
Abstract Introduction Multiple pregnancies are much more common today than they were in the past. Twin pregnancies occur in about 4% of pregnancies in Africa. Adverse pregnancy outcome was more common in twin pregnancy than in singleton pregnancy. There is no pooled evidence on the burden and adverse pregnancy outcome of twin pregnancy in eastern Africa. Thus, this systematic review and meta-analysis were conducted to assess the prevalence and adverse pregnancy outcomes of twin pregnancies. Methods This systematic review and meta-analysis covers published and unpublished studies searched from different databases (PubMed, CINAHL (EBSCO), EMBASE, DOAJ, Web of Sciences, MEDLINE, Cochrane Library, SCOPUS, Google Scholar, and Google search). Finally, 34 studies were included in this systematic review and meta-analysis. JBI checklist was used to assess the quality of included papers. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used. Data synthesis and statistical analysis were conducted using STATA Version 14 software. Heterogeneity and publication bias were assessed. A forest plot was used to present the pooled prevalence using the random effect model. Results The prevalence of twin pregnancy in eastern Africa was 3% [95% CI: 2, 3]. The adverse pregnancy outcomes like neonatal intensive care unit admission (78%), low birth weight (44%), low APGAR score (33%), prematurity (32%), stillbirth (30%), neonatal mortality (12%) and maternal complications like hypertensive disorder of pregnancy (25%), postpartum hemorrhage (7%), Cesarean section (37%), premature rupture of membrane (12%) and maternal mortality are more common among twin pregnancy than singleton pregnancy. Conclusion One in every 33 children born a twin in east Africa; admission to neonatal intensive care unit, low birth weight, low APGAR score, prematurity, stillbirth, neonatal mortality and maternal complications are its associated adverse birth outcomes. Since twin pregnancy is a high-risk pregnancy, special care is needed during pregnancy, labor and delivery to reduce adverse pregnancy outcomes.